Penggunaan Media Visual Interaktif dengan Power Point untuk Anak Usia 5-6 Tahun pada Pendidik PAUD di Era Pandemik - Irna Anjarsari; Siti Nurindah Sari; Atika Zahra Furi; Dian Kusumawati; Khasanah, Khasanah (Universitas Negeri Semarang, 2024)
Based on the results of the survey, there are still many educators who use traditional methods of teaching during the pandemic. The choice of using Power Point soft media in the learning process is considered more effective and easy to apply by PAUD educators who are married and have inadequate thinking power when given more detailed graphic visual media. The purpose of this service activity is to broaden the horizons of PAUD educators in understanding the importance of using interactive media in Early Childhood learning and to determine the ability of PAUD educators to create interactive visual media using Power Point software in the learning process for Early Childhood. The methods used in the implementation of this service are presentation, question and answer, mentoring and training in making interactive visual media in the learning process in the Covid 19 pandemic era. This service activity provides the benefit of adding insight into the importance of using interactive visual media in learning in the pandemic era and increasing the ability of educators to hone creativity through power point software. This service activity is carried out within a period of 4 months and is carried out online, in order to measure the success of the service program, continuous observation is carried out.